Implementación de un microscopio virtual para el curso de Patología General del pregrado en una Facultad de Medicina. - Orellano, Carlos (Revista Medica Herediana)
Objective: To describe the implementation of a virtual microscope (VM) for viewing virtual slides (VL) related to the microscopy practices of the course of General Pathology. Methods: Google Maps application was chosen as the VM's viewer for its easy use and wide diffusion. For generate VL, each group of photographs (taken with a microscope camera head and a 10X ocular lens), according to the objective lens used, was evaluated to determine which had a better viewing area and less image diffusion while zooming. Then, they were segmented by a script to produce an image tile for each viewing level (VL) and saved in one of the School's servers. Results: The photographs taken with the 10X objective were chosen to get six VL (from 0 to 5), being the second, third and fourth levels equivalent to 100X, 200X and 400X respectively. 68,250 image files were produced with a total size of 1110.29 MB. Finally, they were published in the Virtual Space for Teaching of the course. Conclusions: The disposition of microphotographs with a VM was viable according to the defined approaches. Its use should not replace the common microscopy practices, but rather be a complementary tool. For its high similarity with the traditional microscopy, it could be applied in any discipline where the image serves for diagnosis via telemedicine.